Еще о прагматике и датировке пушкинских помет на второй части «Опытов в стихах и прозе» К. Н. Батюшкова [Why and When did Pushkin Leave Marginalia on His Copy of Konstantin Batyushkov’s “Opyty v stikhakh i proze”?] - Balakin, Alexei (Slavica Revalensia, 2016)
The present article is aimed at explaining the pragmatics of Alexander Pushkin’s marginalia on the second volume of Opyty v stikhakh i proze (1817) by Konstantin Batyushkov. Alexei Balakin hypothesizes that it is likely Pushkin’s remarks were those of a person engaged in preparing Opyty for republication. It is possible that the idea of republishing Batyushkov’s book came from Sergey Uvarov, an influential dignitary, who—in order to complete the project—employed an experienced publisher and his protégé Peter Pletnyov. Pletnyov, in turn, asked Pushkin to evaluate the first edition, make deletions, corrections, etc., yet rejected Pushkin’s suggestions at the final stage of the project.